Chara strigosa A. Braun (Characeae) in Poland - Andrzej Hutorowicz; Anders Langangen (Acta Societatis Botanicorum Poloniae, 2014)
Chara strigosa is reported from several lakes in Poland. The finds were published by Izabella Dąmbska in 1966, but have not been recognised internationally, presumably because Dąmbska's article was published in a local paper in Polish. We give a short description of Charetum strigosa first described by Dąmbska. One of the lakes with C. strigosa is reported with luxuriant growth of a blue-green bacteria common in water blooms. There is a need to survey these lakes in order to prevent an increasing eutrophication.